2021
DOI: 10.9734/jeai/2021/v43i830726
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cutting Size on the Performance of Exogenous Auxin IBA in Vegetative Propagation of Rubus erythroclados Mart. ex Hook. f.

Abstract: Aim: The climbing shrub Rubus erythroclados Mart. ex Hook. f. (amora-verde) has great food (fruits) and medicinal (leaves) potential. However, this species remains understudied. The objective of this study was to evaluate the interaction between cutting size and IBA concentration in the vegetative propagation of R. erythroclados by stem cuttings. Study Design: The experimental design used was completely randomized in a 3x5 factorial combination. The cutting size factor was represented by three levels (10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 11 publications
3
1
0
Order By: Relevance
“…This could be related to the mobilization of more sugars and nutrients at the base of cuttings, during adventitious root generation (5). This finding is the same as found by Balestrin et al, (5).…”
Section: Number Of Lateral Branchessupporting
confidence: 93%
See 3 more Smart Citations
“…This could be related to the mobilization of more sugars and nutrients at the base of cuttings, during adventitious root generation (5). This finding is the same as found by Balestrin et al, (5).…”
Section: Number Of Lateral Branchessupporting
confidence: 93%
“…This can also emphasize that, to some extent, the longer the cuttings, the longer the shoots emerged ( 14). This result is consistent with many previous studies' results, i. e.; Balestrin et al, (5) showed that 20-cm cuttings of Rubus erythroclados gave 52.7 cm shoot length which was significantly different compared to 10 and 15cm cuttings giving 18.7 and 41.8 cm shoot lengths, respectively. Kahramanoğlu and Umar (17) also indicated that the length of shoots that emerged from pomegranate cuttings is proportional to cutting length.…”
Section: Shoot Length (Cm)supporting
confidence: 93%
See 2 more Smart Citations